Impact of Pradhan Mantri Ujjwala Yojana on the Forest Dwelling Tribes of Kannur District in Kerala - Dr. M. S. Mahendrakumar (International Journal of Management Studies (IJMS), 2021)
This paper attempts to study the impact of Pradhan Mantri Ujjwala Yojana (PMUY) scheme on the tribes living in the Kannavam Reserve Forest of Kannur District in Kerala and it also tries to analyse the economic activities of the forest dwelling tribes of Kannavam Reserve Forest diachronically. The PMUY scheme was launched on 1st May 2016, which was aimed to provide LPG connections to rural women below poverty line and later it was extended to all SC/ST households and forest dwellers. The tribes of the study area have got LPG connections through the PMUY scheme within the last six months in 2019. Most of the tribal people were unaware of the use of LPG and they continued to use firewood in their kitchens. With the implementation of the LPG scheme, a considerable number of the forest dwelling tribes have got LPG connections and the present paper provides a succinct image on the impact of the PMUY scheme on the forest dwelling tribes and the resultant socio-cultural changes.